Using ground granulated blast-furnace slag to improve the self-degradation issue of liquid calcium aluminate cement mortar - Chia-Jung Tsai; Chung-Lin Lin; Chih-Wei Lu; Wen-Shinn Shyu; Leila Fazeldehkordi (Discover Sustainability)
Abstract This study investigated the potential of liquid calcium aluminate cement (LCAC) as a sustainable substitute in the cement industry. The fluid form of LCAC effectively mitigates the rapid setting issues associated with traditional powdered calcium aluminate cement (CAC) and addresses logistical challenges related to transportation. Despite these advantages, challenges such as hydration conversion and subsequent compressive strength reduction, which can lead to self-degradation, have limited the application of LCAC. In addition, despite the fundamental similarity between LCAC and CAC, the significant differences in practical characteristics, including pH and reaction mechanisms, render traditional CAC methodologies less effective for LCAC. In this research, ground granulated blast-furnace slag (GGBS) was incorporated into LCAC mortar at various proportions to evaluate its potential as an auxiliary material. The findings demonstrated that the addition of GGBS noticeably enhanced the compressive strength and density of LCAC. The findings showed an optimal GGBS addition of 15% resulted in a 42.35% increase in compressive strength and a 31.23% reduction in water absorption. Microscopic structural analyses revealed that GGBS facilitated pozzolanic reactions, leading to the formation of stable Calcium-Aluminosilicate Hydrate (C-A-S-H) and Calcium Silicate Hydrate (C-S-H) gels, which mitigated self-degradation by reducing porosity. This study confirmed that LCAC can effectively address the challenges of hydration conversion and compressive strength reduction similar to CAC. The research highlighted the dual advantages of GGBS, which not only enhances the mechanical properties of LCAC but also fosters sustainability by lowering carbon emissions during both production and long-term application.